Anomalous atomic displacement parameters and local dynamics in the Curie range of a Pb-free relaxor ferroelectric system (Bi1-xBax)(Fe1-xTix)O3 (0.36 ≤ x ≤ 0.50) - Singh A.; Moriyoshi C.; Kuroiwa Y.; Pandey D. (My University, 2025)
We report here the relaxor ferroelectric (RFE) behaviour in a multiferroic solid solution system, (Bi1-xBax)(Fe1-xTix)O3, at a critical disorder level of xC ∼ 0.35 in BiFeO3 and 0.65 (i.e., 1-xC = 0.35) in BaTiO3 similar to the 1:2 ratio of Mg2+ and Nb5+ in the canonical RFE Pb(Mg1/3Nb2/3)O3. This Pb-free system, like canonical Pb-based RFEs, does not exhibit macroscopic symmetry breaking and shows only the signatures of ergodicity breaking at Vogel-Fulcher freezing temperature (TVF). The atomic displacement parameters (ADPs) of Fe3+/Ti4+ and O2-, obtained using high wave vector (Q) and high-resolution synchrotron x-ray diffraction data as a function of temperature, show anomalous diffuse peaks in the Curie range. It is shown that the diffuse peak in ADPs is due to softening of the vibrational frequencies of the B-O chain (B = Fe3+/Ti4+ and O = O2-) below the Burns temperature (TB) followed by hardening below the characteristic temperature (T′m), which corresponds to a peak in the dielectric permittivity (ϵ′). © 2018 Author(s).